DISKURSUS KEILMUAN: Hellenisasi Pemikiran Islam Atau Islamisasi Berbagai Tradisi Keilmuan? - Rusli, Ris'an (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
In the classical period, the scholars built the division of science into two groups namely, the science of religion called â€œal-â€˜ulÃ»m al-dÃ®niyahâ€, and the science of non-religious or â€œal-â€˜ulÃ»m al-dunyawiyahâ€. In the science of religion, they have the science of exegesis, the science of á¸¥adÃ®th, the science of kalÃ¢m, the science of fiqh, and the science of tasawuf. While on non-religious sciences, they have history, medicine, astronomy, chemistry, mathematics, optic, physics, cosmography, and many more. On that time, the scholars were imbued with high appreciation of tought, so they succeeded in making rapid progress in various fields of life, including the field of knowledge and philosophy. The peak of progress occurred at the time of the â€˜AbbÃ¢sids, the previous KhalÃ®fah al-Maâ€™mÃ»n. In the view of Greek or Hellenic thought there were two expert views, rejecting Hellenism or accepting it. The differences lied in the views of Islam, Islam as â€˜aqÃ®dah (creed) and Islam as a civilization. Those who reject Hellenism view Islam as a creed with revelation as the source of knowledge. While those who accept Hellenism view Islam as not a creed, but Islam as civilization.